The Nature of the Eight-factored Ariya, Lokuttara Magga in the Suttas Compared to the Pali Commentarial Idea of it as Momentary - Harvey, Peter (Religions of South Asia, 2014)
It is widely recognized that the key practice of Theravada Buddhism is the ’Noble Eightfold Path’ (ariya atthangika magga). While this is sometimes loosely seen as encompassing all Theravada Buddhist practices, the developed tradition, as expressed in the Pali commentaries, sees it as a momentary state, the culmination of prior practice, that glimpses the transcendent Nibbana and is immediately followed by the attainment of ’fruit’ consciousnesses that signifies becoming a stream-enterer, once-returner, non-returner or Arahat. In the Pali Suttas, however, the noble path can be seen to be a specific kind of calm and open mind state that is a skilful, eight-factored method. Once it arises it is certain to bring stream-entry, and its seeing of Nibbana, later in the present life, but for this it needs to be developed to full strength, which usually takes some period of time, as a person intently works to directly see the unconditioned.